Pfeiffers mark 50th (Raton Range Raton, New Mexico, 1980)
Newspaper Article on the 50th Anniversary of Frank and Kay Pfeiffer.
Master list item #: 2
File location is in the Raton File Cabinet
Keywords: Pfeiffer, Frank; Pfeiffer, Kay; Brown, Joyce; Brown, Bernard; Ruoff, Sue; Ruoff, George; Woolman, Ian; Woolman, Linda; Keller, Pamela; Keller, Bill; Brown, Craig; Ruoff, Katy; Ruoff, Chris; Woolman, Randy; Woolman, Forrest; Kingsbury, Karla; Schulte, Erma; Pirnie, Frances; Baumgradner, Arch; Baumgardner (Mrs); Oppenheim, Phil; Oppenheim (Mrs); Crawford, Dale; Crawford (Mrs); Skie, John; Skie, (Mrs); Skie, Shelly; Looney, Ralph; Looney, (Mrs); Rose, Dwight; Rose, (Mrs); McCrossen, Eric; McCrossen, (Mrs); Cushing, Bud; Cushing, (Mrs); Cordell, Cindy; Johnson, Leon; Johnson, (Mrs.); Crawford, Sharon; Kilmurray, Winifred; Harley, Bill; Harley, (Mrs); Wilkins, Diana; Morga, Mary Margaret; Raton Country Club; St. Vincent's Catholic Church; La Mesa Park; History -- Raton, New Mexico; Biography; Local History; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico; Kansas City, Missouri; Boulder, Colorado; Albuquerque, New Mexico; Conoga Park, California; Milford, Indiana